(3aJM GdCbaGd HTQM eJf JMaI GdCWaGds - (3SdjeGf GdLeRhQi GdTgjQ HGdCafOis; (3GdLeRhQj , GdGafOj,J (B1198 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdaQbGf Ydi YHOg JfRjdkG hHYO , abO WdH efi HYV GdCMHGH Cf CYed dg TQMkG dWjakG eNJUQkG Ydi fXei GdeSei H` aCLHJg s
(3BNQgG (B:s
(3Ke GdUdGI hGdSdGe CHOkG Ydi NJGe GdCfHjGA CMeOG hGdBd hGdUMH hcd JGHY hcd SGeY hTQM gPjf GdHjJjf eYRi Hg ai GdCUd aQGLYJg hgPG BNQ eG jSQ Gddg Je s
(3CQLhRI ai GdJLhjOs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI cJHJ HYV YHGQGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdbQGAGJ hGdJLhjOs